2006
DOI: 10.1007/s00199-006-0153-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting moral wiggle room: experiments demonstrating an illusory preference for fairness

Abstract: Subjects in economic experiments are often generous. This behavior is often interpreted as reflecting a preference for equitable, efficient, or otherwise desirable social outcomes. We show that a considerable proportion of such fair behavior may be driven by a desire to appear fair without actually wanting a fair outcome. To do so, we first demonstrate a high frequency of fair behavior in a modification of the standard dictator game, but then show that fairness decreases substantially when the connection betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

76
859
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,205 publications
(999 citation statements)
references
References 30 publications
76
859
2
5
Order By: Relevance
“…As indicated above, several aspects of dictator behavior seem inconsistent with standard economic models of selfishness or altruism where preferences are defined over material outcomes. For example, Dana et al (2007) compared a binary choice baseline, in which a large majority of dictators preferred the "fair" allocation (5, 5) to the "unfair" alternative (6, 1), with alternative treatments enabling dictators to obscure the relationship between their actions and the resulting outcomes. In these alternative treatments, generosity was significantly lower than in the baseline case.…”
Section: Exit and Motives For Generositymentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated above, several aspects of dictator behavior seem inconsistent with standard economic models of selfishness or altruism where preferences are defined over material outcomes. For example, Dana et al (2007) compared a binary choice baseline, in which a large majority of dictators preferred the "fair" allocation (5, 5) to the "unfair" alternative (6, 1), with alternative treatments enabling dictators to obscure the relationship between their actions and the resulting outcomes. In these alternative treatments, generosity was significantly lower than in the baseline case.…”
Section: Exit and Motives For Generositymentioning
confidence: 99%
“…7 [ Table 1 about here] All subjects participated in one experiment consisting of two parts. 8 The uncertainty in the first of these treatments was introduced partly in order to obscure the consequences for the recipient of exiting, since previous evidence indicates that this decreases subjects' generosity (Dana, Weber and Kuang 2007;Lazear et al 2006). In addition, however, it provides a chance to observe behavior of subjects who prefer to exit, but who are nevertheless placed in a dictator situation.…”
Section: The Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reasoning is related to the notion that people take advantage of "moral wiggle room" to act self-interestedly as shown in Dana et al (2007). They found that, when there is uncertainty about the relationship between a dictator's actions and outcomes, subjects choose more frequently the selfish action.…”
Section: Introductionmentioning
confidence: 82%
“…However, this paper does not take into account the liberal egalitarian concept the experimental design produces little evidence for it. 6 Since utilitarianism is equal to completely selfish behavior, one's self-distribution amount * approaches to a strict utilitarian as one's load factor on material utility 1 approaches one: lim…”
Section: -3 Relative Earningsmentioning
confidence: 99%